Identification and rating of treatment goals in schizophrenia: Delphi process and concordance survey in matched physician-patient pairs - Gründer, Gerhard; Bauknecht, Philipp; Schell, Stefanie; Leopold, Karolina; Paulzen, Michael; Leucht, Stefan (Patient preference and adherence, 2025)
Our primary objective was to evaluate and prioritize treatment goals from a psychiatrists’ and patients’ perspective.
Gesehen am 20.05.2025